From Macumba to Umbanda: the legitimating process of a religion considered somehow authentic Brazilian - Morais, Mariana Ramos de (2019)
This article aims to present the legitimating process of Umbanda as a religion. Umbanda is one of the Afro-Brazilian religions and, nowadays, it is present in all over the country and even in other countries. Different authors affirm that this religion appeared in the Southeast of Brazil in the beginning of the 20th century. The religious practice called “Macumba” and associated to the Black people is thought as the Umbanda’s origin. To affirm this practice as a religion some groups tried to associate it with Spiritism and to define it as an authentic Brazilian religion. Others preferred to exalt its African heritage. This article shows the different ways chosen by those groups, in the first half of the 20th century. Therefore, it presents how the academic literature approaches the conformation of Umbanda and its legitimating process. Moreover, it analyses texts produced by the umbandistas themselves.